2022
DOI: 10.26418/jeltim.v4i1.51770
|View full text |Cite
|
Sign up to set email alerts
|

Developing supplementary materials for descriptive text writing using Ispring Quizmaker

Abstract: This research was conducted to develop supplementary materials to support writing on descriptive text in companion to the English textbook for Seventh Grade. This research is qualitative based, and the method adopted is by development research. The researcher used the ADDIE model as the model of development of this research. However, due to time limitations to accomplish all steps, this research only implemented three phases: analyzing, designing, and developing (ADD). This research used the semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The lack of materials required serious attention, especially since the materials provided by the teacher occasionally fall short of the learning objective (Brilianto et al, n.d.). This problem also found on the previous research by Utami et al, (2022). In that research, the researcher explained that the lack of the materials in the textbook made the students did not interest to participate in teaching-learning in the classroom.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The lack of materials required serious attention, especially since the materials provided by the teacher occasionally fall short of the learning objective (Brilianto et al, n.d.). This problem also found on the previous research by Utami et al, (2022). In that research, the researcher explained that the lack of the materials in the textbook made the students did not interest to participate in teaching-learning in the classroom.…”
Section: Discussionmentioning
confidence: 67%
“…As the gap of this research, the researcher designed supplementary materials of procedure text for senior high school and focus on writing skills. Furthermore, related to the media showing the materials, two previous studies who used multimedia-based to design the materials, were Sauramanda et al, 2022, andUtami et al, 2022. These studies showed the importance of media used in displaying the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Textbooks are the most used teaching materials (Sucipto & Cahyo, 2019). According to Utami et al (2022), teachers tend not only to use textbook materials in their classroom teaching, but also to incorporate them extensively into daily activities and exercises for students. When textbooks are created to implement the curriculum, they will include structured learning objectives, learning activities, learning materials, and learning approaches to help students improve their thinking structure or cognitive achievement.…”
Section: Introductionmentioning
confidence: 99%
“…In the Indonesian experience, the government invited experts to write books, procured reading materials, and evaluated the books before serving them to the students [7]. It is also possible that teachers can collaborate to write reading materials for their students as global or national materials, like what has been done by a student in Pontianak, an expert in Pontianak, and an expert in Pulau Pinang that collaborated in producing a set of teaching materials [8].…”
Section: Introductionmentioning
confidence: 99%